2013
DOI: 10.1007/s10059-013-0078-x
|View full text |Cite
|
Sign up to set email alerts
|

(S)-Tetrahydroisoquinoline Alkaloid Inhibits LPS-Induced Arachidonic Acid Release through Downregulation of cPLA2 Expression

Abstract: Sepsis, a systemic inflammatory response syndrome, remains a potentially lethal condition. (S)-1-α-Naphthylmethyl-6,7-dihydroxy-1,2,3,4-tetrahydroisoquinoline (CKD712) is noted as a drug candidate for sepsis. Many studies have demonstrated its significant anti-inflammatory effects. Here we first examined whether CKD712 inhibits lipopolysaccharide (LPS)-induced arachidonic acid (AA) release in the RAW 264.7 mouse monocyte cell line, and subsequently, its inhibitory mechanisms. CKD712 reversed LPS-associated mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…Interestingly, whereas inflammatory genes were increased in progenitor cells from R26STAT3C stopfl/fl CD4Cre, we saw a significant decrease in IFN-stimulated genes in response to SCFA treatment and an increase in Dusp1, a negative regulator of osteoclast differentiation and a primary mediator of the resolution of inflammation. [24][25] A comprehensive comparison across all our experimental groups of the most significant IFN-stimulated genes from our pathway analysis revealed a remarkable decrease in gene expression among SCFA-treated R26STAT3C stopfl/fl CD4Cre mice, similar to the levels seen in our control groups (Figure 4D). Our findings indicate that SCFAs could modulate osteoclastogenesis by diminishing inflammation through IFN-and STAT1-driven immune responses.…”
Section: Discussionsupporting
confidence: 64%
“…Interestingly, whereas inflammatory genes were increased in progenitor cells from R26STAT3C stopfl/fl CD4Cre, we saw a significant decrease in IFN-stimulated genes in response to SCFA treatment and an increase in Dusp1, a negative regulator of osteoclast differentiation and a primary mediator of the resolution of inflammation. [24][25] A comprehensive comparison across all our experimental groups of the most significant IFN-stimulated genes from our pathway analysis revealed a remarkable decrease in gene expression among SCFA-treated R26STAT3C stopfl/fl CD4Cre mice, similar to the levels seen in our control groups (Figure 4D). Our findings indicate that SCFAs could modulate osteoclastogenesis by diminishing inflammation through IFN-and STAT1-driven immune responses.…”
Section: Discussionsupporting
confidence: 64%
“…Besides, NF‐κB is proven to be an inflammatory central transcription factor activated by receptor for advanced glycation end product (RAGE) with S100A12 gene, and S100A12 was proven to activate the ERK pathway, showing the positive connection among them . Moreover, a previous study showed that inhibition of cPLA2 expression might be a novel target for sepsis, indicating that silencing S100A12 could also inhibit cPLA2 with the positive association . Consistently, S100A12 could activate and represent a variety of signal transduction pathways in combination with Ca 2+ .…”
Section: Discussionmentioning
confidence: 81%
“…Degradation of p53 relieves repression of cyclin B1 transcription, increasing levels of cyclin B1 (Innocente et al, 1999;Krause et al, 2000). In contrast, the direct interaction between BRCA1 and cyclin B1 can prevent its degradation and stabilize cyclin B1 proteins (Choi et al, 2018). Therefore, HPV oncoproteins and BRCA1 have similar effects, to maintain elevated levels of cyclin B1.…”
Section: Discussionmentioning
confidence: 99%